Anteriorising Common Isolates for "Form of Presentation of Data" : Depth Classification Version of CC - Ragavan, M. C.; Arora, Pavan; Gupta, S. P.; Bhatla, K. K. (Journal of Information and Knowledge, 1983)
In the pursuit of research a large amount of data is generated both in the laboratory and in the field. There is a need to store, retrieve and re-utilize the data in an effective and economnical way. Data is presented in a variety of forms in the literature. "These may be in the form of graph" tables" pie-charts, Mapes etc. It has been observed in actual operation of the data bank in the Central Road Research Institute (CRRI), New Delhi that the indexing system should have the capability to indicate the form of presentation of data as this constitutes an approach term i.e. the retrieval term. To meet this need a tentative depth classification version of CC for form of presentation of data, to. be treated as an anteriorising common isolates. has been attempted. Some examples are also cited.